Economies of Scope in Distance Education: The Case of Chinese Research Universities - Li, Fengliang; Chen, Xinlei (International Review of Research in Open and Distributed Learning, 2012)
With the rapid development of information technologies, distance education has become “another form of product differentiation in the output mix produced by the multi-product university or college” (Cohn & Cooper, 2004, p. 607). This article aims at analyzing the economies of scope of distance education (as an educational output) in Chinese research universities. The empirical results show that a) product-specific economies of scope do exist in distance education programs offered by Chinese research universities; b) there are economies of scale in distance education; and c) there are weak cost complementarities between distance education and research output, meaning that distance education and academic research can promote each other to reduce the costs in Chinese research universities.